Work in progress and other stories - Feld, Lisa Batya, author; Schwartz, Steven, 1950-, advisor; Doenges, Judy, 1959-, committee member; Malpezzi Price, Paola, 1948-, committee member (Colorado State University. Libraries, 2011)
This collection of short stories was completed over my course of study in the MFA program in creative writing at Colorado State University. Each of these stories explores the power that family members hold over one another and the ways that power shifts over time.